Peran Istri Buruh Migran dalam Mendukung Kelangsungan Pendidikan Anak di Desa Pohgading Timur Kecamatan Pringgabaya Kabupaten Lombok Timur - Wiwik Agustina; Bagdawansyah Alqadri; Mohammad Mustari (Mataram University, 2026)
Economic demands often force husbands to migrate for work, leaving wives with the dual responsibility of managing the household and ensuring their children's education. This situation significantly affects the continuity and stability of children's learning development. This study aims to analyze the role of migrant workers' wives in supporting the continuity of children's education and identify supporting and inhibiting factors in Pohgading Timur Village, Pringgabaya District, East Lombok Regency. This study uses a qualitative approach with migrant workers' wives and children as subjects, while the informants include teachers and village secretaries. Data were collected through observation, interviews, and documentation, then analyzed using an interactive analysis model that includes data reduction, data presentation, and drawing conclusions. The results show that migrant workers' wives play a role as caregivers, family financial managers, and educational motivators in supporting the continuity of children's education. Supporting factors include parental guidance and a positive environment, while inhibiting factors include family financial pressure and limited parental time to accompany children's education. The results of the study can be concluded that migrant workers' wives have a very important role in maintaining the continuity of children's education through care, financial management, and motivation. Therefore, cooperation between families, schools, and communities is needed to support the continuity of children's education.